2007
DOI: 10.4049/jimmunol.179.10.6673
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Melanoma Cell Adhesion Molecule (MCAM)/CD146 in Lymphocyte Endothelium Interaction: MCAM/CD146 Promotes Rolling via Microvilli Induction in Lymphocyte and Is an Endothelial Adhesion Receptor

Abstract: The melanoma cell adhesion molecule (MCAM)/CD146 is expressed as two isoforms differing by their cytoplasmic domain (MCAM long (MCAM-l) and MCAM short (MCAM-s)). MCAM being expressed by endothelial cells and activated T cells, we analyzed its involvement in lymphocyte trafficking. The NK cell line NKL1 was transfected by MCAM isoforms and submitted to adhesion on both the endothelial cell monolayer and recombinant molecules under shear stress. MCAM-l transfection reduced rolling velocity and increased NKL1 adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 68 publications
8
93
1
Order By: Relevance
“…The levels of CD146 transcripts were measured by quantitative RT-PCR. Two isoforms of CD146 were previously reported in human endothelial cells and Guezguez et al have reported that the ectopic expression of each isoform in the CD146-negative NKL1 human NK cell line confers to these cells distinct adhesive properties to endothelial cells [23,24]. We found that both isoforms are expressed by the three subsets of NK cells and the transcript levels correlated with those of CD146 protein detected in these subsets (Fig.…”
Section: Cd146 Expression Is Acquired Upon Nk Cell Maturationsupporting
confidence: 74%
“…The levels of CD146 transcripts were measured by quantitative RT-PCR. Two isoforms of CD146 were previously reported in human endothelial cells and Guezguez et al have reported that the ectopic expression of each isoform in the CD146-negative NKL1 human NK cell line confers to these cells distinct adhesive properties to endothelial cells [23,24]. We found that both isoforms are expressed by the three subsets of NK cells and the transcript levels correlated with those of CD146 protein detected in these subsets (Fig.…”
Section: Cd146 Expression Is Acquired Upon Nk Cell Maturationsupporting
confidence: 74%
“…1D). Many of these molecules have been shown to mediate adhesion (14,15). Cells cultured in IL-2 plus IL-7 expressed more NKG2D and CD94 than cells cultured in IL-7 alone (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…11 MCAM function has been extensively studied in melanomas and other types of cancer (prostate cancer and breast cancer), but the ligand for MCAM has not yet been identified. [12][13][14] This study aimed to clarify the impact of MCAM expression on the functional properties of hMSC and the maintenance of HSPC in co-culture. Thus, we generated primary hMSC that stably expressed shRNA against MCAM or that over-expressed an MCAM coding sequence (CDS) through lentiviral vector gene transfer.…”
Section: Introductionmentioning
confidence: 99%